PARTISIPASI DALAM PENGEMBANGAN PARIWISATA DI DESA GOTOWASI KECAMATAN MABA SELATAN KABUPATEN HALMAHERA TIMUR - Idris, Sri Dewi; Mawara, Jetty E. T.; Mulianti, Titiek (Universitas Sam Ratulangi, 2021)
The abundance of existing natural resources can increase economic growth when the resources can be managed properly in accordance with what is most in demand by the community so that the utilization of natural resources will not spend time or material due to the failure to manage a resource. Tourism is one of the utilization of natural resources that can be of high economic value for an area that manages natural resources into a tourist attraction that can attract visitors both from within and outside the country, in addition to high economic value, tourism can grow and increase the sense of pride in the nation so that it will grow people who care more about a nation.North Maluku Province has a lot of potential and natural resources that can be developed as a tourist attraction. East Halmahera regency is one of the districts has a potential natural resources for the development of tourism industry. Tourism in Gotowasi Village is one of the village icons that is currently being vigorously promoted by the Tourism and Culture Office of East Halmahera Regency.Community as the main component in the development of community-based tourism has an important role in supporting the development of tourism aimed at developing local potentials sourced from nature, socio-cultural or economic communities. Community participation in maintaining natural resources and culture is a big contribution and has the potential to become a tourist attraction.Keywords: potential, tourism, participation